Land use, biodiversity conservation, and rural development in the dehesas of Cuatro Lugares, Spain - Plieninger, T; Wilbrand, C (Agroforestry Systems, 2001)
Dehesas are an agrosilvopastoral system that has enhanced the maintenance of an extraordinarily high biodiversity. The traditional use is characterized by mixed livestock raising at low stocking densities, employment of hardy regional breeds and an elaborated maintenance and exploitation of holm oaks. Livestock production has traditionally been accompanied by arable systems with long rotations and closed nutrient cycles without external inputs of fodder, fertilizers and agro-chemicals. Modern trends are a specialization toward lamb and beef production and the employment of intensive techniques like freerange grazing at high stocking levels or crossbreeding with high-performance breeds. A model income statement shows that livestock create an income of 49.91 US$ per ewe per year on an average basis. The central problem for the continuity of the dehesas is the gradual decay of the tree canopy. Intensification of agricultural production and the abandonment of traditional grazing practices additionally threaten biodiversity within the dehesas. The authors suggest the foundation of a biosphere reserve in Cuatro Lugares as a framework for a sustainable development of the dehesas.
Keywords: economic output; Grazing; livestock; Mediterranean; pastoralism; Quercus ilex; rangeland

Land use, biodiversity conservation, and rural development in the dehesas of Cuatro Lugares, Spain - Plieninger, T.; Wilbrand, C. (Agroforestry Systems, 2001)
Dehesas are an agrosilvopastoral system that has enhanced the maintenance of an extraordinarily high biodiversity. The traditional use is characterized by mixed livestock raising at low stocking densities, employment of hardy regional breeds and an elaborated maintenance and exploitation of holm oaks. Livestock production has traditionally been accompanied by arable systems with long rotations and closed nutrient cycles without external inputs of fodder, fertilizers and agro-chemicals. Modern trends are a specialization toward lamb and beef production and the employment of intensive techniques like freerange grazing at high stocking levels or crossbreeding with high-performance breeds. A model income statement shows that livestock create an income of 49.91 US$ per ewe per year on an average basis. The central problem for the continuity of the dehesas is the gradual decay of the tree canopy. Intensification of agricultural production and the abandonment of traditional grazing practices additionally threaten biodiversity within the dehesas. The authors suggest the foundation of a biosphere reserve in Cuatro Lugares as a framework for a sustainable development of the dehesas.
Keywords: economic output; Grazing; livestock; Mediterranean; pastoralism; Quercus ilex; rangeland